An Analysis of Politeness Strategies in English Textbook Dialogues on Faith and Morality - Mutiara Hanif Saputri; Djatmika; Fauziati, Endang (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
Faith and morality have been parts of Indonesian society. The values of Pancasila as the national ideology are sufficient to proof that this nation’s relationship with faith and morality has been inseparable. This study aims to analyze one of the dimensions of the Pancasila Student Profile, “faith, devotion to God Almighty, and noble character,” through the application of politeness strategies in textbook dialogues. The method of this study is qualitative content analysis. The data collection technique of this study is documentation. The data are in the form of dialogue texts from two textbooks from the series of “Buku PR Interaktif Bahasa Inggris.” This study implements the politeness strategy by Brown and Levinson (1987) and the Pancasila Student Profile as part of Indonesia’s character education as the frameworks of this study. After collecting and categorizing the data using those two frameworks, the results of this study show two elements of “faith, devotion to God Almighty, and noble character” to be represented through politeness strategies in the dialogue texts in both of the textbooks. These elements are “moral towards humans” and “moral towards nature.” The results suggest textbook authors to include more balanced representation of all elements within “faith, devotion to God Almighty, and noble character” in order to develop students’ character to be well-rounded individuals. These results also suggest teachers to utilize the textbook dialogues through various activities such as roleplay, group reading, and group discussion to help students learn various types of morality in interactive ways.